DIALEKTIKA FILSAFAT DALAM SEJARAH ISLAM: PEMIKIRAN DAN PROBLEMATIKANYA - Nazhif Muhammad; Achmad Reza Hutama Al-Faruqi (Academic Journal of Islamic Principles and Philosophy, 2022)
Islamic philosophy has a long history of problems, both within and outside the Muslim body. Philosophy that originated in Greece has certainly given rise to judgment, condemnation, and even rejection from some Islamic circles. Al-Ghazālī (1058-1111 AD) with his book Tahāfut al-Falāsifah, which later made the stigma about philosophy worse and even led to his death, and which later appeared on the counter of an Ibn Rusyd with his book Tahafut At-Tahafut. This article highlights the thinking of Muslim philosophers and scholars in response to philosophy and mentions the reasons behind it, which will then be packaged in the form of the ups and downs of the development of Islamic philosophy. This article will also help decipher the origins of philosophy, its position in the tradition of thinking in Islam, and philosophy as a fusion between revelation and reason. This article's discussion uses a descriptive-analytical method that focuses on history. The results of this study can help recognize the role and position of philosophy in the intellectual history of Islam, which is then able to determine attitudes and views towards philosophy.